Penerapan Teknologi Content Delivery Network (CDN) untuk Mendukung Digitalisasi Sekolah di Daerah 3T - Nana Rachmana Syambas; Syaiful Ahdan; Eki Ahmad Zaki Hamidi; Ratna Mayasari; Ade Nurhayati; Galih Nugraha Nurkahfi; Jupriyadi Jupriyadi; Adi Sucipto; Hasan Nur Arifin; Rohmat Tulloh (Universitas Nurul Jadid, 2025)
This Community Service Program was implemented at SMKS Bumi Moro, Pulau Morotai Regency, a school located in a frontier, outermost, and underdeveloped (3T) region. The school was selected due to its limited telecommunication infrastructure, which has significantly constrained the implementation of digital learning. An initial survey revealed that the school relied on a single unstable internet access point, had only 12 active computers for approximately 180 students, and most teachers lacked experience in independently operating a Learning Management System (LMS). These conditions highlighted the urgent need for technological intervention. The program adopted a Participatory Action Research (PAR) approach consisting of four stages: (1) needs analysis through online surveys and interviews with the school principal and 20 teachers; (2) design and implementation of a local Content Delivery Network (CDN) integrated with Starlink-based internet connectivity; (3) training and mentoring on Moodle LMS utilization and the introduction of Artificial Intelligence (AI) applications in learning; and (4) evaluation of program effectiveness. The training involved 30 participants, including 20 teachers and 10 educational staff members. Evaluation using a Likert-scale questionnaire (1–5) showed that 70% of participants were very satisfied and 30% were satisfied, with average scores ranging from 4.6 to 4.9. Post-program observations indicated improved teacher capacity in managing digital classes, conducting online assessments, and utilizing stable internet access. Overall, the program successfully strengthened digital learning infrastructure and teacher competence, offering a replicable model for other schools in 3T regions in Indonesia.